gl-subgroups and Isomorphism Theorems of gl-groups - Parimi Radhakrishna Kishore; Sileshe Gone Korma (International Journal of Mathematics And its Applications, 2023)
A generalized lattice ordered group (gl-group) is a partially ordered group (po-group) in which the underlying poset is a generalized lattice. This paper deals with the concept of gl-subgroup of a gl-group. Introduced the concept of gl-subgroup and proved that the quotient of a gl-group by its normal convex gl-subgroup is again a gl-group. Later, introduced the concept of gl-homomorphism and obtained the isomorphism theorems of gl-groups.